2013
DOI: 10.1200/jco.2013.31.15_suppl.8019
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter effort to identify driver mutations and employ targeted therapy in patients with lung adenocarcinomas: The Lung Cancer Mutation Consortium (LCMC).

Abstract: 8019 Background: The detection of driver mutations in the EGFR and ALK genes and targeted therapy has transformed treatment of lung cancer. The LCMC was established in 2009 to assay lung adenocarcinomas for driver genomic alterations in 10 genes and to study and treat patients by their molecular subtypes. Methods: The 14-member LCMC enrolled patients with metastatic adenocarcinoma of the lung and tested their tumors in CLIA laboratories for KRAS, EGFR, HER2, BRAF, PIK3CA, AKT1, MEK1, and NRAS mutations using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 0 publications
1
30
0
3
Order By: Relevance
“…29 Among patients with lung adenocarcinoma, driver mutations have been identified in 62% of patients undergoing testing for at least 1 genomic alteration. 100 Mutations in BRAF arise in 1.6% to 4.9% of adenocarcinomas. 1,12,13,101,102 Unlike melanoma, PTC, and HCL in which most BRAF mutations are V600E, mutations in lung adenocarcinomas can be separated into either V600E (50%-56.8%) and non-V600E (43.2%-50%).…”
Section: Non-small-cell Lung Cancermentioning
confidence: 99%
“…29 Among patients with lung adenocarcinoma, driver mutations have been identified in 62% of patients undergoing testing for at least 1 genomic alteration. 100 Mutations in BRAF arise in 1.6% to 4.9% of adenocarcinomas. 1,12,13,101,102 Unlike melanoma, PTC, and HCL in which most BRAF mutations are V600E, mutations in lung adenocarcinomas can be separated into either V600E (50%-56.8%) and non-V600E (43.2%-50%).…”
Section: Non-small-cell Lung Cancermentioning
confidence: 99%
“…However, our survival in chemotherapy arm was consistent with survival data reported in chemotherapy trials. A meta-analysis that included individual patient data from 2968 patients in nine trials, comparing cisplatin based to carboplatin based chemotherapy showed median survival of (median 8.4 vs. 9.1 months, HR for death 1.07, 95% CI 0.99 -1.15) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Data from the Lung Cancer Mutation Consortium (LCMC) identified an oncogenic driver in 62% of lung adenocarcinomas that undergo molecular profiling for 10 of the most common oncogenic drivers and that these oncogenic drivers are 97% mutually exclusive. 21 When tissue availability is an issue, it is reasonable to do molecular testing concurrently for the currently actionable genotypes (EGFR and ALK), then proceed to more extensive profiling if these initial tests are negative, to triage a patient to a clinical trial for a potentially actionable mutation. 21 If tissue and resources allow, one can also consider testing more broadly as part of the initial oncogenic screen, and consider utilizing a next-generation sequencing (NGS) platform, which includes both the actionable and the putative oncogenic drivers, as well as genotypic abnormalities for which the functional or therapeutic significance is as yet unknown.…”
Section: Practical Considerations In Molecular Testingmentioning
confidence: 99%
“…1). 21,23 The recognition of the central role of targeted therapy in EGFR-mutant lung adenocarcinoma is rooted in the landmark Iressa Pan-Asia Study (IPASS), a randomized phase 3 clinical trial that evaluated the efficacy of gefitinib versus carboplatin/paclitaxel as first-line therapy in patients clinically selected on the basis of adenocarcinoma histology, Asian ethnicity, and never-or light-smoking status. 24 The IPASS clinical trial illustrates first and foremost that targeted therapy with the EGFR TKI gefitinib is superior to conventional chemotherapy in the EGFR mutant population and is associated with a 71.2% response rate (RR) and a 52% relative risk reduction for progression-free survival (PFS) compared with chemotherapy (p < 0.001; ►Table 1).…”
Section: Actionable Oncogenic Drivers In Nsclc Egfrmentioning
confidence: 99%
See 1 more Smart Citation